Cellular and Synaptic Localization of EAAT2a in Human Cerebral Cortex - Melone, Marcello; Bellesi, Michele; Ducati, Alessandro; Iacoangeli, Maurizio; Conti, Fiorenzo (Frontiers in Neuroanatomy, 2011)
We used light and electron microscopic immunocytochemical techniques to analyze the distribution, cellular and synaptic localization of EAAT2, the main glutamate transporter, in normal human neocortex. EAAT2a immunoreactivity was in all layers and consisted of small neuropilar puncta and rare cells. In white matter EAAT2a+ cells were numerous. Electron microscopic studies showed that in gray matter ∼77% of immunoreactive elements were astrocytic processes, ∼14% axon terminals, ∼2.8% dendrites, whereas ∼5% were unidentifiable. In white matter, ∼81% were astrocytic processes, ∼17% were myelinated axons and ∼2.0% were unidentified. EAAT2a immunoreactivity was never in microglial cells and oligodendrocytes. Pre-embedding electron microscopy showed that ∼67% of EAAT2a expressed at (or in the vicinity of) asymmetric synapses was in astrocytes, ∼17% in axon terminals, while ∼13% was both in astrocytes and in axons. Post-embeddeding electron microscopy studies showed that in astrocytic processes contacting asymmetric synapses and in axon terminals, gold particle density was ∼25.1 and ∼2.8 particles/µm2, respectively, and was concentrated in a membrane region extending for ∼300 nm from the active zone edge. Besides representing the first detailed description of EAAT2a in human cerebral cortex, these findings may contribute to understanding its role in the pathophysiology of neuropsychiatric diseases.